Pyrolysis of Napier grass to bio-oil and catalytic upgrading to high grade bio-fuel - Mohammed, Isah Yakub (2017)
Biomass is one of the renewable energy resources that has carbon in its building blocks that can be processed into liquid fuel. Napier grass biomass is a herbaceous lignocellulosic material with potentials of high biomass yield. Utilization of Napier grass for bio-oil production via pyrolysis is very limited. Bio-oil generally has poor physicochemical properties such as low pH value, high water content, poor chemical and thermal stabilities which makes it unsuitable for direct use as fuel and therefore requires further processing. Upgrading of bio-oil to liquid fuel is still at early stage of research. Several studies are being carried out to upgrade bio-oil to transportation fuel. However, issues regarding reaction mechanisms and catalyst deactivation amongst others remain a challenge.